Streptococcal Siglec-like adhesins recognize different subsets of human plasma glycoproteins: implications for infective endocarditis. (14th June 2018) - Bensing, Barbara A; Li, Qiongyu; Park, Dayoung; Lebrilla, Carlito B; Sullam, Paul M
Abstract: Streptococcus gordonii and Streptococcus sanguinis are typically found among the normal oral microbiota but can also cause infective endocarditis. These organisms express cell surface serine-rich repeat adhesins containing "Siglec-like" binding regions (SLBRs) that mediate attachment to α2-3-linked sialic acids on human glycoproteins. Two known receptors for the Siglec-like adhesins are the salivary mucin MG2/MUC7 and platelet GPIbα, and the interaction of streptococci with these targets may contribute to oral colonization and endocarditis, respectively. The SLBRs display a surprising diversity of preferences for defined glycans, ranging from highly selective to broader specificity. In this report, we characterize the glycoproteins in human plasma recognized by four SLBRs that prefer different α2-3 sialoglycan structures. We found that the SLBRs recognize a surprisingly small subset of plasma proteins that are extensively O -glycosylated. The preferred plasma protein ligands for a sialyl-T antigen-selective SLBR are proteoglycan 4 (lubricin) and inter-alpha-trypsin inhibitor heavy chain H4. Conversely, the preferred ligand for a 3′sialyllactosamine-selective SLBR is glycocalicin (the extracellular portion of platelet GPIbα). All four SLBRs recognize C1 inhibitor but detect distinctly different glycoforms of this key regulator of the complement and kallikrein protease cascades. The four plasma ligands have potential roles in thrombosis and inflammation, and each has been cited as a biomarker for one or more vascular or other diseases. The combined results suggest that the interaction of Siglec-like adhesins with different subsets of plasma glycoproteins could have a significant impact on the propensity of streptococci to establish endocardial infections.